(untitled) (Tri-Chandra Journal of Anthropology, 2024)
Unlike the other social science disciplines, anthropology has a broader scope in terms of its theory and methods. It is a holistic discipline which covers all aspects of human being. Nepal has relatively short history of anthropology as teaching discipline. However, it has more than two hundred years of research tradition in Nepal. A score of foreign and native anthropologists have been carried out the research in Nepal. Compare to other disciplines, there are relatively getting research fund from the foreign universities and development agencies. Recent data of the central department of anthropology shows that employment rate of the pass out students in master’s degree in anthropology is higher. But why the number of students enrolled in graduate and undergraduate is low. Taking this issue into consideration, this paper answers the question of low number of student enrolment in the various constituent colleges of Tribhuvan University. The Paper is based on ethnographic interviews with some graduate/ undergraduate students and faculty of Tribhuvan University. There are some reasons to be a low number of students in anthropology: Anthropology demands rigorous and continuous study on the subject matter where original texts are taught. In Nepal, people not only common people but also intellectual including professionals have little knowledge about the distinction between sociology and anthropology due to a long experience of joint department, Tribhuvan University. Importantly, there is no realization from Tribhuvan University administration and Government of Nepal why anthropology is important for the development of the nation. Paper answers these issues.